Personalized Antihypertensive Treatment Optimization With Smartphone‐Enabled Remote Precision Dosing of Amlodipine During the COVID‐19 Pandemic (PERSONAL‐CovidBP Trial) - Collier, David J.; Taylor, Mike; Godec, Thomas; Shiel, Julian; James, Rebecca; Chowdury, Yasmin; Ebano, Patrizia; Monk, Vivienne; Patel, Mital; Pheby, Jane; Pheby, Ruby; Foubister, Amanda; et al. (Journal of the American Heart Association, 2024)
The objective of the PERSONAL-CovidBP (Personalised Electronic Record Supported Optimisation When Alone for Patients With Hypertension: Pilot Study for Remote Medical Management of Hypertension During the COVID-19 Pandemic) trial was to assess the efficacy and safety of smartphone-enabled remote precision dosing of amlodipine to control blood pressure (BP) in participants with primary hypertension during the COVID-19 pandemic. This was an open-label, remote, dose titration trial using daily home self-monitoring of BP, drug dose, and side effects with linked smartphone app and telemonitoring. Participants aged ≥18 years with uncontrolled hypertension (5-7 day baseline mean ≥135 mm Hg systolic BP or ≥85 mm Hg diastolic BP) received personalized amlodipine dose titration using novel (1, 2, 3, 4, 6, 7, 8, 9 mg) and standard (5 and 10 mg) doses daily over 14 weeks. The primary outcome of the trial was mean change in systolic BP from baseline to end of treatment. A total of 205 participants were enrolled and mean BP fell from 142/87 (systolic BP/diastolic BP) to 131/81 mm Hg (a reduction of 11 (95% CI, 10-12)/7 (95% CI, 6-7) mm Hg, <0.001). The majority of participants achieved BP control on novel doses (84%); of those participants, 35% were controlled by 1 mg daily. The majority (88%) controlled on novel doses had no peripheral edema. Adherence to BP recording and reported adherence to medication was 84% and 94%, respectively. Patient retention was 96% (196/205). Treatment was well tolerated with no withdrawals from adverse events. Personalized dose titration with amlodipine was safe, well tolerated, and efficacious in treating primary hypertension. The majority of participants achieved BP control on novel doses, and with personalization of dose there were no trial discontinuations due to drug intolerance. App-assisted remote clinician dose titration may better balance BP control and adverse effects and help optimize long-term care. URL: clinicaltrials.gov. Identifier: NCT04559074.